EU-MERCOSUR trade agreement : finding winners products for Paraguay - Enciso Cano, Víctor (2017)
The European Union (EU) and the Southern Common Market (MERCOSUR) have been negotiating a Regional Association Agreement (RAA) since the mid-nineties. This paper aims to identify products at the level of sub-headings of the Harmonized System which would benefit from the signing of the agreement. The methodology used trade indicators combined with trade statistics from 2010 to 2012. A total of 61 subheadings were identified with potential to increase its exports to the EU with the agreement. At first glance they reproduced the traditional pattern of exports from the MERCOSUR countries, a high concentration in agrifood products due to high exported value of one product. When this product was not considered an important number of manufactures were identified as having potential to increase their exports to the EU. This finding showed a potential to decrease the dependence on primary or raw material exports. The paper focused on tariffs; therefore further research on non-tariff measures for market access is a must.